Are Czechs influenced by the Relative Age Effect? - Dzholdoshev, Semen (2014)
Consequences of an advantage a child gains whenever he is relatively more mature than his competition from the same cohort are called theRelative Age Effect (RAE). The RAE has been of insterest to researchers throughout the world since the 1960s. Proper understanding of this issue would help us with eradication of the DWL created by inefficient selection processes. Up to this point, imperfect statistical methods were used for examining the RAE. Economists have begun to attempt to fix that. This paper continues with that work by applying the instrumental variable approach on data from the Czech Republic. Data from the Czech Tennis Association and a primary school were collected and analysed. The RAE was not found in the primary school, most likely due to insufficient data set and consequential omitted variable bias. Weak, but statistically significant RAE was found in Czech tennis competitions.